Biodegradable quaternary ammonium salt disinfection resin material as well as preparation method and application thereof

By introducing quaternary ammonium salt groups into the adhesive material skeleton and forming a mesoporous structure, the problem of difficult degradation and low disinfection effect of existing quaternary ammonium disinfection resin materials is solved, and an efficient and environmentally friendly disinfection effect is achieved.

CN119409852APending Publication Date: 2025-02-11LOGISTICAL ENGINEERING UNIVERSITY OF PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771190.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing quaternary ammonium disinfectant resin materials are difficult to degrade after use, which can easily cause secondary pollution to the environment and have low disinfection effect.

Method used

采用壳聚糖、卡拉胶或海藻酸钠等胶黏性材料作为树脂骨架,引入季铵盐基团,并通过枝接和交联反应形成介孔结构,增强材料的抗菌性能和热稳定性。

Benefits of technology

The biodegradability of quaternary ammonium disinfection resin materials has been achieved, which reduces environmental pollution and significantly improves the disinfection effect, especially for efficient removal of Gram-negative and positive bacteria.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409852A_ABST
    Figure CN119409852A_ABST
Patent Text Reader

Abstract

The invention relates to a biodegradable quaternary ammonium salt disinfection resin material as well as a preparation method and application thereof. The biodegradable quaternary ammonium salt disinfection resin material comprises a resin skeleton and a quaternary ammonium salt group doped in the resin skeleton. The invention also provides a preparation method of the quaternary ammonium salt disinfection resin material, which comprises the following steps: dissolving the adhesive material in an organic acid solution, then adding quaternary ammonium salt, then adding the continuous phase solvent, the pore-forming agent, the emulsifier and the initiator, and continuously heating and carrying out primary stirring reaction in the reagent adding process to promote the reverse emulsion polymerization of the mixed slurry into a liquid drop system; and adding an alkaline solution into the liquid drop system, continuously heating to a second temperature, and carrying out secondary stirring reaction to promote the liquid drops to be cured into particles, thereby obtaining the quaternary ammonium salt disinfection resin material. The invention also provides application of the ammonium salt disinfection resin material as a contact disinfection material in drinking water. The problems that an existing quaternary ammonium salt disinfection resin material is difficult to degrade after being used and easily causes secondary pollution to the environment are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment functional materials, and in particular to a biodegradable quaternary ammonium salt disinfection resin material and a preparation method and application thereof. Background Art

[0002] Biosafety is the most important aspect of ensuring the safety of drinking water quality. Therefore, countries and international organizations around the world have set strict and clear standards for sanitary bacteriological indicators such as total colony count and pathogenic microorganisms. In the process of municipal water treatment, although conventional pre-treatment methods such as coagulation, sedimentation and filtration can remove a large number of pathogens, disinfection technology is still a key step in ensuring the biosafety of drinking water, which constitutes the last line of defense against waterborne pathogens invading the human body.

[0003] Emergency drinking water purification equipment is different from conventional municipal water treatment facilities. They must be portable, easy to maintain, and highly adaptable to different water sources. Therefore, these devices place higher requirements on the effectiveness of disinfection components. At present, the design of the disinfection function of emergency drinking water purification is mainly divided into two ideas: one is to manually add prefabricated disinfection tablets through a mixer, and the other is to use an ultraviolet disinfector. However, both methods have certain limitations. The manual addition of prefabricated disinfection tablets is contrary to the portability requirements of emergency devices, and disinfectants are usually highly corrosive, inconvenient to carry, short in validity, and easy to fail, which cannot meet the needs of long-term storage; while ultraviolet disinfection does not require the addition of agents, but its bactericidal ability is greatly affected by the turbidity of water quality, and the disinfection efficiency decreases when the turbidity increases. In addition, ultraviolet rays have poor inhibitory effects on the activity of some Gram-positive bacteria, which cannot meet the requirements of high adaptability of emergency devices to water sources, and there is a biosafety risk.

[0004] Quaternary ammonium compounds are a class of cationic surfactants with unique bactericidal functions. They were first synthesized through the irreversible reaction of tertiary amines and halogenated hydrocarbons. Since their discovery, quaternary ammonium compounds have been widely used in many fields, including industrial use, water treatment, garden sterilization, as well as medicine and daily consumer products. Despite this, the bactericidal mechanism of quaternary ammonium salts is not yet fully understood. Existing studies have shown that their bactericidal properties mainly originate from the hydrophobic and electrostatic interactions between quaternary ammonium salts and the bacterial surface. These forces cause the quaternary ammonium groups to attach to the cell surface, thereby causing the death of microorganisms by destroying the phospholipid bilayer on the cell membrane, consuming the membrane proton driving force, and interfering with the activity of membrane-bound enzymes. The basic structure of quaternary ammonium salts is as follows: Figure 1As shown, the negatively charged part is an anion, which is usually a quaternary ammonium salt formed by the combination of Br and N atoms, and the R group can be an alkyl chain in any form. According to the development and molecular weight of quaternary ammonium disinfectants, quaternary ammonium disinfection compounds can be divided into small molecule quaternary ammonium disinfectants and high molecular quaternary ammonium disinfectants. However, the positive electrical properties of existing quaternary ammonium disinfectant molecules are easily disturbed by coexisting media in water, resulting in insufficient affinity between pathogenic bacteria cell membranes, thereby affecting contact with bacteria, resulting in a decrease in disinfection effect; and for high molecular quaternary ammonium disinfectants, they have the problem of being difficult to degrade and digest after use, which is easy to cause secondary pollution to the environment.

[0005] Chitosan is a derivative of chitosan produced by hydrolysis of chitosan under alkaline conditions and removal of some acetyl groups. It is also called chitosan, aminopolysaccharide or chitosan, and its chemical name is β-(1→4)-2-amino-2-deoxy-D-glucose. In nature, the annual biosynthesis of chitosan is about 10 billion tons, which is the second largest organic resource on earth after cellulose, providing a huge resource treasure house for mankind. The sources of chitosan are extremely rich. Studies have shown that chitosan and its processed products are a kind of green, environmentally friendly, renewable biomass material with biodegradability. Summary of the invention

[0006] The purpose of the present invention is to provide a biodegradable quaternary ammonium salt disinfection resin material and a preparation method and application thereof, so as to solve the problem that the existing quaternary ammonium salt disinfection resin material is difficult to degrade after use and easily causes secondary pollution to the environment, and can also solve the problem that the existing quaternary ammonium salt disinfectant has a low disinfection effect.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A biodegradable quaternary ammonium salt disinfection resin material, comprising a resin skeleton and quaternary ammonium salt groups doped in the resin skeleton;

[0009] The raw material of the resin skeleton is selected from adhesive materials;

[0010] The adhesive material is selected from at least one of chitosan, carrageenan and sodium alginate.

[0011] According to the above-mentioned technical means, by introducing quaternary ammonium salt groups in the adhesive material skeleton, after the quaternary ammonium salt groups are grafted, the cross-linking sites with the chitosan matrix are reduced, so that the internal collapse forms a mesoporous structure, which is very conducive to the adsorption effect, thereby effectively enhancing the antibacterial properties of the material, and combining the natural antibacterial properties of quaternary ammonium salts, effectively inhibiting the growth of bacteria and fungi. The introduction of quaternary ammonium salt groups effectively improves the thermal stability of the material, thereby still maintaining the performance of the material at higher temperatures. The positive charge characteristics of the quaternary ammonium salt group can enhance the interaction of the material with other negatively charged surfaces, thereby improving the cyclic stability of the disinfection resin material. And adhesive materials such as chitosan, carrageenan and sodium alginate have good biocompatibility and biodegradability, which makes the final quaternary ammonium salt disinfection resin material can be degraded by environmental friendliness after use, reducing pollution to the environment. Secondly, these adhesive materials usually have good adhesion properties, which can ensure the stable attachment of the quaternary ammonium salt group on the application surface, thereby improving the durability of the disinfection effect. In addition, the porous structure of the adhesive material can provide a larger contact area for the quaternary ammonium salt groups, effectively enhancing the antibacterial activity.

[0012] Using a beaker static contact experiment, quaternary ammonium resin was used as a disinfectant to control pathogens in drinking water. It was found that the quaternary ammonium groups on the resin surface can separate and firmly bind pathogens from the water body through electrostatic adsorption. During the adsorption process, the quaternary ammonium carbon chain groups will further destroy the cell membrane structure of pathogens, trigger cytoplasmic dissolution, and eventually lead to their death. Comparative experiments found that the efficiency of quaternary ammonium resin in removing Gram-negative and Gram-positive bacteria represented by Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus is stronger than that of silver-loaded activated carbon. It was also found that under the conditions of a resin dosage of 100 BV and a reaction time of 1 h, the average removal efficiency of quaternary ammonium resin for the four bacteria was between 79.8% and 93.7%, which was higher than the 65.3% to 77.9% of silver-loaded activated carbon. Taking Staphylococcus aureus as a model bacterium, through experiments on the influence of multiple operating parameters and environmental factors, it was found that the gradient changes of ionic strength (NaCl: 0.5-0.9wt%), temperature (10-30℃) and natural organic matter NOM concentration (2-10mg / L) had no significant effect on the sterilization effect of quaternary ammonium resin. At the same time, the quaternary ammonium resin maintained a stable sterilization ability during the four cycles of use, and the sterilization rate of Staphylococcus aureus was maintained at more than 90%. The quaternary ammonium resin was filled into the filter column, and a dynamic disinfection test was carried out using several surface waters in Chongqing as raw water. It was found that the resin can play an excellent contact disinfection effect, and the total number of colonies and the number of Escherichia coli in the effluent meet the relevant requirements of the national "Sanitary Standards for Drinking Water" (GB 5749-2022), and the failure time point is as high as 10000BV. Therefore, using quaternary ammonium drinking water disinfection resin as a disinfection material for emergency water purification equipment can effectively play the role of a biological safety barrier. In addition, through long-term underground burial experiments, it was found that the resin can be gradually biodegraded and absorbed after failure, which will not increase the cost of secondary treatment and has good environmental compatibility. This effectively solves the problem that the existing quaternary ammonium salt disinfection resin materials are difficult to degrade after use and are prone to secondary pollution to the environment.

[0013] Preferably, the biodegradable quaternary ammonium salt disinfection resin material is obtained by inverse emulsion polymerization of the adhesive material and the quaternary ammonium salt.

[0014] Preferably, the quaternary ammonium salt disinfection resin material is in the form of small particles.

[0015] Preferably, the quaternary ammonium salt is selected from at least one of 2,3-epoxypropyltrimethylammonium chloride, didodecyldimethylammonium chloride and benzyltrimethylammonium chloride.

[0016] Preferably, the quaternary ammonium salt is selected from 2,3-epoxypropyltrimethylammonium chloride.

[0017] Preferably, the adhesive material is selected from chitosan.

[0018] Preferably, the mass ratio of the adhesive material to the quaternary ammonium salt is 100:2-10.

[0019] By precisely controlling the mass ratio of adhesive material to quaternary ammonium salt to 100:2-10, the problem of insufficient functionalized sites of quaternary ammonium salt caused by excessively high mass ratio and the problem of poor slurry viscosity and poor curing effect of emulsion polymerization caused by too low solid-liquid ratio can be effectively avoided.

[0020] The present invention also provides a method for preparing the biodegradable quaternary ammonium salt disinfection resin material according to the present invention, comprising the following steps:

[0021] S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution;

[0022] S2, adding a quaternary ammonium salt to the adhesive aqueous solution to obtain a quaternary ammonium salt adhesive slurry;

[0023] S3, adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, and continuously heating the mixed slurry during the process of adding the continuous phase solvent, the pore-forming agent, the emulsifier and the initiator, stirring the reaction once, and promoting the reverse emulsion polymerization of the mixed slurry into a droplet system;

[0024] S4, adding an alkaline solution to the droplet system and continuing to raise the temperature to a second temperature, stirring a second time to carry out a cross-linking reaction, so as to cause the droplets to solidify into particles, and obtain a quaternary ammonium salt disinfection resin material.

[0025] By using adhesive material, organic acid solution, quaternary ammonium salt, continuous phase solvent, pore-forming agent, emulsifier and initiator, these compositions can be decomposed by microorganisms in the environment after use, reducing secondary pollution to the environment. By dissolving the adhesive material in the organic acid solution, then adding quaternary ammonium salt and other necessary components, the whole preparation process steps are clear, easy to operate and control, and are particularly suitable for industrialized production. Quaternary ammonium salt has good disinfection and sterilization effect, and the disinfection resin material obtained by the preparation method of the present invention can effectively kill bacteria and viruses, and is applicable to multiple disinfection occasions. By adding alkaline solution and controlling temperature in the droplet system, accurate control of particle solidification can be achieved, thereby obtaining the disinfection resin particles of required size and shape.

[0026] Preferably, the solid-liquid ratio of the adhesive material to the organic acid is 1 g to 10 g: 100 mL.

[0027] Preferably, the organic acid solution is selected from at least one of a formic acid solution, an acetic acid solution and a propionic acid solution.

[0028] Preferably, the volume concentration of the organic acid in the organic acid solution is 1-3%.

[0029] Preferably, S2 comprises: adding a quaternary ammonium salt to the adhesive aqueous solution, reacting at room temperature for 0.5 to 4 hours, to obtain a quaternary ammonium salt adhesive slurry.

[0030] Preferably, the continuous phase solvent is selected from organic solvents that are less dense than water and immiscible with water.

[0031] Preferably, the continuous phase solvent is selected from at least one of liquid paraffin, mineral oil, silicone oil and synthetic hydrocarbons.

[0032] Preferably, the volume ratio of the continuous phase solvent to the quaternized adhesive slurry is 1:3 to 2:1.

[0033] Preferably, the pore former is selected from liquid organic substances that are volatile and insoluble in water.

[0034] Preferably, the pore-forming agent is selected from at least one of ethyl acetate, chloroform and styrene.

[0035] Preferably, the volume ratio of the pore-forming agent to the mixed slurry is 2 to 10:100.

[0036] Preferably, the emulsifier is selected from ester nonionic surfactants.

[0037] Preferably, the emulsifier is selected from at least one of Tween series (Tween 20, Tween 40, Tween 60, Tween 80), Span series (Span 20, Span 40, Span 60, Span 80), sucrose fatty acid esters, propylene glycol fatty acid esters and mono- and di-stearyl glycerides.

[0038] Preferably, the volume ratio of the emulsifier to the mixed slurry is 1 to 6:100.

[0039] Preferably, the initiator is selected from agents that can react with amino groups on the adhesive material via a Schiff base reaction.

[0040] Preferably, the initiator is selected from at least one of aldehyde compounds such as formaldehyde, acetaldehyde, malondialdehyde, glutaraldehyde, and epoxy compounds such as propylene oxide, epichlorohydrin, and epoxy alcohol.

[0041] Preferably, the volume ratio of the initiator to the mixed slurry is 3 to 15:100.

[0042] Preferably, the temperature is continuously raised between 40 and 60° C. during the process of adding the continuous phase solvent, pore former, emulsifier and initiator.

[0043] Preferably, the second temperature is 70°C to 85°C.

[0044] Among them, the heating method can be an electric heating jacket or a water bath.

[0045] Preferably, the rotation speed of the primary stirring reaction is 400-900 rpm.

[0046] The first stirring is vigorous stirring, specifically: with the intervention of a mechanical stirrer, a stirring paddle is used to mix the solution system after adding the continuous phase solvent, the pore former, the emulsifier and the initiator at a rate of 400 to 900 rpm.

[0047] Preferably, the time of the stirring reaction is 30 to 220 minutes.

[0048] Preferably, the rotation speed of the secondary stirring reaction is 200-400 rpm.

[0049] Preferably, the secondary stirring reaction time is 2 to 6 hours.

[0050] Preferably, in S4, the alkaline solution is added dropwise.

[0051] Preferably, the alkaline solution is selected from at least one of a potassium hydroxide solution, a sodium hydroxide solution and an ammonia solution.

[0052] Preferably, the concentration of the alkali in the alkaline solution is above 1 mol / L.

[0053] Preferably, the pH value of the alkaline solution is greater than 12.5.

[0054] Preferably, the method for preparing the quaternary ammonium salt disinfection resin material comprises the following steps:

[0055] S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution;

[0056] S2, adding 2,3-epoxypropyltrimethylammonium chloride (ETA) powder to the adhesive aqueous solution, stirring with a mechanical stirrer to completely dissolve the adhesive material, and reacting at room temperature for 0.5 to 4 hours until a translucent golden colloidal solution is obtained to obtain a quaternary ammonium salt adhesive slurry;

[0057] S3, sequentially adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, heating the mixture to a first temperature, stirring the mixture to react, and causing the mixed slurry to undergo reverse emulsion polymerization to form a droplet system;

[0058] S4, adding alkaline solution dropwise to the droplet system and continuing to raise the temperature to a second temperature, stirring the reaction a second time to cause the droplets to solidify into particles, separating, washing, and drying to obtain a quaternary ammonium salt disinfection resin material.

[0059] Preferably, the separation is to use a filter to directly separate the granular solidified material generated at the bottom from the reaction solution.

[0060] Preferably, the washing is to use an organic solvent and deionized water to alternately wash the separated granular solidified material, the alternation number of times is 3 times, wherein the organic solvent washing adopts a Soxhlet extractor, and the solvent specifically uses non-polar hydrocarbons such as petroleum ether, and the time is controlled within 6 hours; the deionized water washing method is repeated immersion, and the washing completion mark is that the pH of the deionized water washing eluate is between 6 and 8.

[0061] Preferably, the drying is to naturally air-dry or bake the washed granular solidified material. Natural air-drying specifically includes: placing the washed granular solidified material in a sieve and placing it in a ventilated place for 2 to 3 days; drying is performed in an electric blast drying oven with a drying setting temperature below 50°C and a drying time of 8h to 12h.

[0062] The present invention also provides an application of the biodegradable quaternary ammonium salt disinfection resin material prepared by the preparation method of the present invention as a contact disinfection material in drinking water.

[0063] Among them, biodegradable quaternary ammonium resin was used as a disinfection material to control pathogenic bacteria in drinking water. It was found that the quaternary ammonium groups on the resin surface can separate and firmly bind pathogenic bacteria from the water body through electrostatic adsorption. During the adsorption process, the biodegradable quaternary ammonium carbon chain groups will further destroy the cell membrane structure of the pathogenic bacteria, induce cytoplasmic dissolution, and ultimately lead to their death.

[0064] Preferably, the biodegradable quaternary ammonium salt disinfection resin material is used as a disinfection component in a drinking water emergency water purification device.

[0065] Preferably, the biodegradable quaternary ammonium salt disinfection resin material is filled in a disinfection component of an emergency water purification device that uses outdoor water sources as raw water, and is used as a quick-contact disinfection material.

[0066] Preferably, the biodegradable quaternary ammonium salt disinfection resin material is used as a contact disinfection filter material when an emergency water purification device uses a field water source as raw water.

[0067] Preferably, the biodegradable quaternary ammonium salt disinfection resin material still has antibacterial ability after continuous water filtration of 10,000 BV, and can be directly buried and biodegraded after failure, thereby achieving harmless utilization of the material throughout the entire process.

[0068] Preferably, the disinfected pathogenic bacteria include at least one of Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus.

[0069] Preferably, the used biodegradable quaternary ammonium salt disinfection resin material is washed with a sodium chloride solution to remove surface microbial debris, and the concentration of sodium chloride in the sodium chloride solution is controlled between 3% and 18%.

[0070] Preferably, the concentration of sodium chloride in the sodium chloride solution is 10%.

[0071] Among them, when the biodegradable quaternary ammonium salt disinfection resin material is actually used, the quaternary ammonium salt disinfection resin material is filled into a filter column, and the drinking water can be disinfected by filtering it in direct contact with the drinking water.

[0072] Preferably, the biodegradable quaternary ammonium salt disinfection resin material is directly landfilled and biodegrades on its own after it becomes ineffective, so as to achieve harmlessness throughout the entire life cycle of the material.

[0073] The beneficial effects of the present invention are as follows:

[0074] The quaternary ammonium salt disinfection resin material of the present invention is innovatively based on polysaccharide adhesive natural compounds as a skeleton, and by introducing quaternary ammonium salt groups in the adhesive material skeleton, after the quaternary ammonium salt groups are grafted, the cross-linking sites with the chitosan matrix are reduced, so that the internal collapse forms a mesoporous structure, and the mesoporous structure is very conducive to the adsorption effect, and therefore, the antibacterial properties of the material are enhanced by the synergistic effect of chitosan and the quaternary ammonium salt groups. Because the quaternary ammonium salt has natural antibacterial properties, it can effectively inhibit the growth of bacteria and fungi. The introduction of the quaternary ammonium salt group effectively improves the thermal stability of the material, thereby still maintaining the performance of the material at a higher temperature. The positive charge characteristics of the quaternary ammonium salt group can enhance the interaction between the material and other negatively charged surfaces, thereby improving the cyclic stability of the disinfection resin material. And adhesive materials such as chitosan, carrageenan and sodium alginate usually contain a large amount of hydroxyl and amino electrical resistance groups, which can reduce the electrical neutralization interference brought to the material surface by the coexisting medium in water, so it can ensure that the quaternary ammonium salt positive ion group adheres to the stable state of the application surface, thereby improving the durability of the disinfection effect. In addition, the porous structure of the adhesive material can provide a large contact area, thereby effectively enhancing the antibacterial activity. Secondly, these adhesive materials have good biocompatibility and biodegradability, which allows the final quaternary ammonium salt disinfection resin material to be environmentally friendly degraded after use, reducing pollution to the environment. In addition, the relatively low price and wide source of adhesive materials such as chitosan, carrageenan and sodium alginate help reduce production costs.

[0075] The preparation method of quaternary ammonium salt disinfection resin material of the present invention, by using adhesive material, organic acid solution, quaternary ammonium salt, continuous phase solvent, pore-forming agent, emulsifier and initiator, these compositions can be decomposed by microorganisms in the environment after use, and the secondary pollution to the environment is reduced.Quaternary ammonium salt has good disinfection and sterilization effect, and the disinfection resin material obtained by the preparation method of the present invention can effectively kill bacteria and viruses, and is applicable to multiple disinfection occasions.By adding alkaline solution and controlling temperature in the droplet system, accurate control of particle solidification can be realized, thereby obtaining the disinfection resin particles of required size and shape.In addition, the preparation method has the advantages of easy and simple operation, easy operation control and gentle process conditions, is particularly suitable for industrialized production, and has extensive promotion and practical value in the field of water treatment functional material technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 The following are actual comparison photos of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 and the common chitosan polymer resin prepared in Control Example 1;

[0077] Figure 2 The infrared spectra of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1, the common chitosan polymer resin prepared in Control Example 1, and the chitosan powder;

[0078] Figure 3 The SEM images of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 and the common chitosan polymer resin in Control Example 1;

[0079] Figure 4 The figure is a result diagram of the removal rate of four model bacteria by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 at different dosages;

[0080] Figure 5 The removal rate results and corresponding kinetic curves of four model bacteria in aqueous solution by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1, the common chitosan polymer resin prepared in Control Example 1 and the purchased commercially available silver-loaded activated carbon particles;

[0081] Figure 6 The figure is a result diagram of the removal rate of four model bacteria in aqueous solutions at different temperatures by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1;

[0082] Figure 7 The figure is a result diagram of the removal rate of four model bacteria in aqueous solutions with different ionic strengths by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1;

[0083] Figure 8The figure is a result of the removal rate of four model bacteria in aqueous solutions with different natural organic matter contents by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 and the traditional high molecular quaternary ammonium salt disinfection material prepared in Control Example 2;

[0084] Fig. 9 The results are the removal rates of four model bacteria in aqueous solution by the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 after multiple cycles and regeneration;

[0085] Fig.10 Schematic diagram of the device for dynamic disinfection performance test.

[0086] Fig.11 This is a graph showing the soil landfill degradation test results of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1, the ordinary chitosan polymer resin prepared in Control Example 1, and the traditional high molecular quaternary ammonium salt disinfection material prepared in Control Example 2. DETAILED DESCRIPTION

[0087] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0088] Example 1

[0089] like Figure 1 As shown, a method for preparing a biodegradable quaternary ammonium salt disinfection resin material comprises the following steps:

[0090] S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution, specifically comprising:

[0091] 5 g of chitosan powder was placed in a beaker, and 100 mL of acetic acid solution with a concentration of 2% acetic acid was added, and mechanical stirring was performed at a rate of 300 rpm for 2 h to ensure complete dissolution, to obtain a uniform khaki viscous gel-like chitosan solution;

[0092] S2, adding a quaternary ammonium salt to an adhesive aqueous solution to obtain a quaternary ammonium salt adhesive slurry, specifically comprising:

[0093] Add 10 g of 2,3-epoxypropyltrimethylammonium chloride (ETA) to the chitosan solution obtained in S1, and stir the reaction at room temperature for 4 h. At this time, the viscous yellowish-brown solution turns into light gray, which is the quaternized chitosan slurry.

[0094] S3, adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, heating it to a first temperature, stirring it once to react, and causing the mixed slurry to reverse emulsion polymerize into a droplet system, specifically comprising:

[0095] S31, taking 40 mL of the quaternary ammonium salt chitosan slurry obtained in S2, adding 50 mL of liquid paraffin, and increasing the stirring rate to 600 rpm until the slurry is fully broken up and suspended in the paraffin in a filamentous state, to obtain a first mixed slurry;

[0096] S32, adding 5 mL of ethyl acetate to the first mixed slurry obtained in S31, stirring at a stirring rate of 600 rpm for 3 min to obtain a second mixed slurry;

[0097] S33, adding 4 mL of Tween-80 emulsifier to the second mixed slurry obtained in S32, then reducing the stirring rate to 300 rpm, and raising the temperature to 50° C. and keeping the temperature for 20 min to obtain a third mixed slurry;

[0098] S34, heating the third mixed slurry obtained in S33 to 60° C., adding 3.2 mL of formaldehyde solution to perform a pre-crosslinking reaction after the heating is completed, and then immediately increasing the rotation speed to 400 rpm and keeping the temperature for 30 minutes to obtain a droplet system;

[0099] S4, adding an alkaline solution to the droplet system and continuing to heat it to a second temperature, stirring and reacting for a second time, causing the droplets to solidify into particles, and obtaining a quaternary ammonium salt disinfection resin material, specifically comprising:

[0100] S41. Add 5 mL of glutaraldehyde to the droplet system obtained in S34, and slowly drip 35 mL of 1 mol / L NaOH solution to carry out cross-linking reaction. When the amount of NaOH solution dripped exceeds 10 mL, the slurry system will begin to become viscous. At this time, increase the speed to 700 rpm and continue dripping. After the viscosity is significantly reduced and the resistance of the stirring paddle is reduced, restore the speed to 300 rpm. Use a pH meter to monitor the pH of the solution. When the pH exceeds 11, stop continuously dripping NaOH solution, set the water bath to 70°C, and set the agitator speed to 200 rpm, and keep warm for 2 hours. At this time, a large amount of solids can be seen at the bottom of the reactor. Thereafter, measure the pH every 5 minutes, and intermittently drip NaOH to ensure that the system pH is between 9.5 and 11 until the granular solids are no longer generated;

[0101] S42. Filter the granular solid system obtained in S41 to separate the granular solidified material from the reaction solution to obtain the granular solidified material at the bottom; place the granular solidified material in a Soxhlet extractor, and extract it with petroleum ether as the eluent for 12 hours, then use ethanol and water to directly soak and wash the solid material three times alternately until the eluate is neutral, and separate and collect the granular solidified material; place the collected granular solidified material on a sieve, and place it in a ventilated place for 2 to 3 days to obtain a biodegradable quaternary ammonium salt disinfection resin material for use.

[0102] Example 2

[0103] like Figure 1 As shown, a method for preparing a biodegradable quaternary ammonium salt disinfection resin material comprises the following steps:

[0104] S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution, specifically comprising:

[0105] Take 5g of carrageenan powder in a beaker, add 100mL of acetic acid solution with a concentration of 2% acetic acid, and stir mechanically at a rate of 300rpm for 2h to ensure complete dissolution, to obtain a uniform khaki viscous gel-like carrageenan solution;

[0106] S2, adding a quaternary ammonium salt to an adhesive aqueous solution to obtain a quaternary ammonium salt adhesive slurry, specifically comprising:

[0107] Add 10 g of 2,3-epoxypropyltrimethylammonium chloride (ETA) to the carrageenan solution obtained in S1, and stir the reaction at room temperature for 4 h. At this time, the viscous yellowish-brown solution turns into light gray, which is the quaternized chitosan slurry.

[0108] S3, adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, heating it to a first temperature, stirring it once to react, and causing the mixed slurry to reverse emulsion polymerize into a droplet system, specifically comprising:

[0109] S31, taking 40 mL of the quaternary ammonium salt chitosan slurry obtained in S2, adding 50 mL of liquid paraffin, and increasing the stirring rate to 600 rpm until the slurry is fully broken up and suspended in the paraffin in a filamentous state, to obtain a first mixed slurry;

[0110] S32, adding 5 mL of ethyl acetate to the first mixed slurry obtained in S31, stirring at a stirring rate of 600 rpm for 3 min to obtain a second mixed slurry;

[0111] S33, adding 4 mL of Tween-80 emulsifier to the second mixed slurry obtained in S32, then reducing the stirring rate to 300 rpm, and raising the temperature to 50° C. and keeping the temperature for 20 min to obtain a third mixed slurry;

[0112] S34, heating the third mixed slurry obtained in S33 to 60° C., adding 3.2 mL of formaldehyde solution to perform a pre-crosslinking reaction after the heating is completed, and then immediately increasing the rotation speed to 400 rpm and keeping the temperature for 30 minutes to obtain a droplet system;

[0113] S4, adding an alkaline solution to the droplet system and continuing to heat it to a second temperature, stirring and reacting for a second time, causing the droplets to solidify into particles, and obtaining a quaternary ammonium salt disinfection resin material, specifically comprising:

[0114] S41. Add 5 mL of glutaraldehyde to the droplet system obtained in S34, and slowly drip 35 mL of 1 mol / L NaOH solution to carry out a cross-linking reaction. When the amount of NaOH solution dripped exceeds 10 mL, the slurry system will begin to become viscous. At this time, increase the speed to 700 rpm and continue dripping. When the viscosity is significantly reduced and the resistance of the stirring paddle is reduced, restore the speed to 300 rpm. Use a pH meter to monitor the pH of the solution. When the pH exceeds 11, stop continuously dripping the NaOH solution, set the water bath to 70°C, and set the agitator speed to 200 rpm, and keep warm for 2 hours. At this time, a large amount of solids can be seen at the bottom of the reactor. Thereafter, measure the pH every 5 minutes, and intermittently drip NaOH to ensure that the system pH is between 9.5 and 11 until the granular solids are no longer generated;

[0115] S42. Filter the granular solid system obtained in S41 to separate the granular solidified material from the reaction solution to obtain the granular solidified material at the bottom; place the granular solidified material in a Soxhlet extractor, and extract it with petroleum ether as the eluent for 12 hours, then use ethanol and water to directly soak and wash the solid material three times alternately until the eluate is neutral, and separate and collect the granular solidified material; place the collected granular solidified material on a sieve, and place it in a ventilated place for 2 to 3 days to obtain a biodegradable quaternary ammonium salt disinfection resin material for use.

[0116] Example 3

[0117] like Figure 1 As shown, a method for preparing a biodegradable quaternary ammonium salt disinfection resin material comprises the following steps:

[0118] S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution, specifically comprising:

[0119] Take 5 g of sodium alginate powder in a beaker, add 100 mL of acetic acid solution with a concentration of 2% acetic acid, and stir mechanically at a rate of 300 rpm for 2 h to ensure complete dissolution, and obtain a uniform khaki viscous gel-like sodium alginate solution;

[0120] S2, adding a quaternary ammonium salt to an adhesive aqueous solution to obtain a quaternary ammonium salt adhesive slurry, specifically comprising:

[0121] Add 10 g of 2,3-epoxypropyltrimethylammonium chloride (ETA) to the sodium alginate solution obtained in S1, and stir the reaction at room temperature for 4 h. At this time, the viscous yellowish-brown solution turns into light gray, which is the quaternized chitosan slurry.

[0122] S3, adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, heating it to a first temperature, stirring it once to react, and causing the mixed slurry to reverse emulsion polymerize into a droplet system, specifically comprising:

[0123] S31, taking 40 mL of the quaternary ammonium salt chitosan slurry obtained in S2, adding 50 mL of liquid paraffin, and increasing the stirring rate to 600 rpm until the slurry is fully broken up and suspended in the paraffin in a filamentous state, to obtain a first mixed slurry;

[0124] S32, adding 5 mL of ethyl acetate to the first mixed slurry obtained in S31, stirring at a stirring rate of 600 rpm for 3 min to obtain a second mixed slurry;

[0125] S33, adding 4 mL of Tween-80 emulsifier to the second mixed slurry obtained in S32, then reducing the stirring rate to 300 rpm, and raising the temperature to 50° C. and keeping the temperature for 20 min to obtain a third mixed slurry;

[0126] S34, heating the third mixed slurry obtained in S33 to 60° C., adding 3.2 mL of formaldehyde solution to perform a pre-crosslinking reaction after the heating is completed, and then immediately increasing the rotation speed to 400 rpm and keeping the temperature for 30 minutes to obtain a droplet system;

[0127] S4, adding an alkaline solution to the droplet system and continuing to heat it to a second temperature, stirring and reacting for a second time, causing the droplets to solidify into particles, and obtaining a quaternary ammonium salt disinfection resin material, specifically comprising:

[0128] S41. Add 5 mL of glutaraldehyde to the droplet system obtained in S34, and slowly drip 35 mL of 1 mol / L NaOH solution. When the amount of NaOH solution dripped exceeds 10 mL, the slurry system will begin to become viscous. At this time, increase the speed to 700 rpm and continue dripping. When the viscosity is significantly reduced and the resistance of the stirring paddle is reduced, restore the speed to 300 rpm. Use a pH meter to monitor the pH of the solution. When the pH exceeds 11, stop dripping the NaOH solution continuously, set the water bath to 70°C, and set the agitator speed to 200 rpm, and keep warm for 2 hours. At this time, a large amount of solids can be seen at the bottom of the reactor. Thereafter, measure the pH every 5 minutes, and intermittently drip NaOH to ensure that the system pH is between 9.5 and 11 until the granular solids are no longer generated;

[0129] S42. Filter the granular solid system obtained in S41 to separate the granular solidified material from the reaction solution to obtain the granular solidified material at the bottom; place the granular solidified material in a Soxhlet extractor, and extract it with petroleum ether as the eluent for 12 hours, then use ethanol and water to directly soak and wash the solid material three times alternately until the eluate is neutral, and separate and collect the granular solidified material; place the collected granular solidified material on a sieve, and place it in a ventilated place for 2 to 3 days to obtain a biodegradable quaternary ammonium salt disinfection resin material for use.

[0130] Comparative Example 1

[0131] A method for preparing a chitosan polymer resin material comprises the following steps:

[0132] S1. Weigh 5 g of chitosan powder into a beaker, add 100 mL of 2% acetic acid solution, and stir mechanically at 300 rpm for 2 h to ensure complete dissolution, to obtain a uniform khaki viscous gel-like chitosan solution;

[0133] S2, subjecting the viscous colloidal chitosan solution described in S1 to emulsion dispersion reverse polymerization, adding an alkaline solution for solidification, and then washing and drying to obtain a chitosan polymer resin material, specifically comprising:

[0134] S21, take 40 mL of the chitosan slurry obtained in S1, add 50 mL of liquid paraffin, increase the stirring rate to 600 rpm until the slurry is fully dispersed and suspended in the paraffin in a filamentous state, add 5 mL of ethyl acetate, keep stirring for 3 min, add 4 mL of Tween-80 dispersant, then reduce the stirring rate back to 300 rpm, and raise the temperature to 50°C and keep warm for 20 min;

[0135] S22, set the temperature to 60°C, add 3.2 mL of formaldehyde solution after the temperature is raised, and then immediately set the speed to 400 rpm and keep warm for 30 minutes;

[0136] S23, add 5mL of glutaraldehyde to the S32 system, and slowly drip 35mL of 1mol / L NaOH solution. When the NaOH dripping exceeds 10mL, the solution will begin to become viscous. At this time, set the speed to 700rpm and continue dripping. When the viscosity is significantly reduced and the resistance of the stirring paddle is reduced, restore the speed to 300rpm. Use a pH meter to monitor the pH of the solution. When the pH exceeds 11, stop dripping the NaOH solution continuously, set the water bath to 70℃, and set the agitator speed to 200rpm, and keep warm for 2h. At this time, a large amount of solids can be seen at the bottom of the reactor. Measure the pH every 5 minutes, and intermittently drip NaOH to ensure that the system pH is between 9.5 and 11;

[0137] S24. Filter the S33 system and place the solids at the bottom in a Soxhlet extractor. Use petroleum ether as the eluent to extract for 12 hours. Then use ethanol and water to directly soak and wash the solids three times alternately until the eluate is neutral. Separate and collect for later use.

[0138] Comparative Example 2

[0139] The preparation method of a small molecule quaternary ammonium salt disinfectant or a high molecular quaternary ammonium salt disinfectant comprises the following steps:

[0140] The present invention uses the same quaternary ammonium salt compound as a modifier and a traditional acrylic resin as a skeleton to prepare a traditional typical polymer quaternary ammonium salt disinfectant as a control material to reflect the synergistic enhanced disinfection effect produced by the proposed adhesive skeleton materials such as chitosan and the quaternary ammonium salt compound.

[0141] The diameter of typical acrylic macroporous resin particles is between 0.15 and 0.18 mm. First, the purchased acrylic polymer particles are washed in the order of sodium hydroxide solution (NaOH), hydrogen chloride (HCl), and distilled water. During the washing process, the volume ratio of the washing solution to the material is maintained at 1000:1 (1000BV). Subsequently, a 1:1 methanol-ethanol mixed solution is used for continuous extraction for 24 hours at an extraction rate of 10 mL / min. Next, the extracted particles are dispersed in 100 times the volume of distilled water, stirred, and the same mass of 2,3-epoxypropyltrimethylammonium chloride (ETA) is added. Stirring is continued for 4 hours at room temperature to complete the quaternary ammonium group surface; finally, a sodium chloride solution with a mass fraction of 15% is used as an ion fixative to convert part of the quaternary ammonium groups that lose positive charge during the synthesis process into a cationic form, and then washed three times with deionized water and stored in deionized water for later use.

[0142] Detection and analysis

[0143] 1) Macroscopic morphology photos

[0144] A small amount of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 and the ordinary chitosan polymer resin prepared in Control Example 1 were taken out and placed on two filter papers for comparison and photographing. The results are as follows: Figure 1 shown.

[0145] from Figure 1 It can be seen that both the biodegradable quaternary ammonium salt disinfection resin material and the ordinary chitosan resin are small spherical particles. The color of the biodegradable quaternary ammonium salt disinfection resin material is lighter than that of the ordinary chitosan resin, which is light yellow, while the chitosan resin is obviously golden yellow.

[0146] 2) Infrared spectrum test

[0147] The biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1, the common chitosan polymer resin prepared in Control Example 1, and the chitosan powder were subjected to infrared spectroscopy test, wherein the conditions of the infrared spectroscopy test were: ATR diffuse reflection mode, wave number setting 400-4000cm -1 , American Thermoelectric Nicolet is50 Fourier transform infrared spectrometer, the results are as follows Figure 2 shown.

[0148] Figure 2 The quaternary ammonium salt disinfection resin, cross-linked chitosan and chitosan respectively represent the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1, the common chitosan polymer particles prepared in Control Example 1 and chitosan powder.

[0149] from Figure 2 The comparative analysis shows that the quaternary ammonium salt disinfection resin (i.e., the biodegradable quaternary ammonium salt disinfection resin material obtained in Example 1) has typical infrared absorption characteristics of chitosan functional groups. -1 ~3500cm -1 The broad absorption band is the chitosan pendant amino C 2 -NH 2 (NH) and C 3 -OH and C 6 -OH stretching vibration characteristics of two hydroxyl groups; 1500cm -1 ~1700cm -1 The absorption band between 850cm -1 ~1200cm -1 The absorption band that appears is the absorption peak group of the oxygen glycosidic bond. In addition, due to the pre-quaternization treatment before emulsion polymerization, the quaternized polymer resin particles are still at 1780cm -1 and 1510cm -1 Two additional absorption peaks appeared at the quaternary ammonium positive ion unit -N + (CH3 ) 3 The bending vibration characteristic peak of the quaternary ammonium salt resin material is at 2750cm -1 ~3000cm -1 The characteristic peaks of the alkyl groups between them have been significantly enhanced, which is also due to the more -CH 3 The appearance of the above characteristic peaks and absorption bands fully proves that the quaternary ammonium groups have been successfully introduced into the surface of the chitosan matrix, thereby successfully synthesizing the quaternary ammonium salt chitosan polymer particles.

[0150] 3) Scanning electron microscopy analysis

[0151] The biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 and the ordinary chitosan polymer resin in Control Example 1 were characterized by scanning electron microscopy. The results are as follows: Figure 3 shown.

[0152] Figure 3 The chitosan resin refers to the common chitosan cross-linked polymer resin prepared in Control Example 1, and the quaternary ammonium salt refers to the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1.

[0153] from Figure 3 Analysis shows that the chitosan polymer particles treated with quaternary ammonium salt (i.e., the quaternary ammonium salt drinking water disinfection resin material obtained in Example 1) are not much different in particle size from the ordinary chitosan polymer particles (the ordinary chitosan polymer resin obtained in Control Example 1). The image shows that the diameter of the spherical particles is about 0.5 mm, and the surfaces of both are relatively smooth under low magnification observation of 300 times, and the degree of spherical regularity is also similar. At a higher magnification of 4000 times, it can be observed that the surface of the polymer obtained by quaternary ammonium salt slurry cross-linking is obviously rougher; further at a higher magnification of 100,000 times, it can be found that compared with ordinary chitosan cross-linked polymers prepared by the same method, the surface of the quaternary ammonium salt cross-linked resin particles has a large number of pores, and the pore size distribution is about 50nm, which is a typical mesoporous structure. This may be due to the fact that after the quaternary ammonium salt group is grafted, the cross-linking sites of the chitosan matrix are reduced, resulting in internal collapse, which is very beneficial to the adsorption effect, and is beneficial to increase the affinity of the resin to the bacterial outer membrane, so that it can more firmly capture pathogens, and is more conducive to the tip contact effect to break them.

[0154] 4) Pathogen removal rate test

[0155] (a) Preparation of bacterial solution

[0156] Pathogenic bacteria are added to water in the form of bacterial liquid. Before carrying out the pathogen removal test, the stock bacterial liquid must be prepared in advance. The bacterial liquid used in this study was made by bacterial strain expansion. The four model pathogenic bacteria strains used for expansion were: Escherichia coli (E.coil.), Pseudomonas aeruginosa (P.aeruginosa.PAO1), Bacillus subtilis (B.subtilis.ATCC10719) and Staphylococcus aureus (S.aureus.ATCC25923).

[0157] After the purchased freeze-dried powder of the bacterial strain is thawed at room temperature, it is added to the sterilized newly prepared nutrient broth, and then placed in a constant temperature shaking incubator (set the speed to 200 rpm, the temperature is 37°C for Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, and 30°C for Bacillus subtilis, 24h) to reach the logarithmic growth period of the bacteria. After the insulation is completed, the bacterial solution is frozen and centrifuged (10,000 rpm, 5min, 4°C), and washed three times with sterile phosphate buffer (SPS, 0.9% sodium chloride solution, pH7) to remove the residual culture medium matrix to obtain a pure model bacterial particle precipitate. Subsequently, it is dispersed into a suspension with SPS, diluted and adjusted, and its OD value is calibrated using a UV spectrophotometer to ensure that the concentration of the bacterial suspension is between 10 7 CFU / mL, refrigerate at 4℃ until use.

[0158] (b) Experiment on the effect of resin dosage on sterilization behavior

[0159] Take 1 mL of the prepared bacterial suspension into a 250 mL sterile conical flask and dilute to 100 mL with sterile phosphate buffer solution (SPS), keeping the initial bacterial suspension concentration at 10 5 CFU / mL, which is equivalent to the amount of microorganisms in the lake water used in the dynamic column experiment. 0.1, 0.5, 1.0, 1.5, 2.0 and 3.0 mL of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 were added to the solution respectively, and placed in a constant temperature shaking shaker for contact reaction to fully mix the resin and the water sample. The speed was set to 150 rpm / min, the reaction was carried out at room temperature, and the reaction time was 1 hour. The removal rates of the four model bacteria corresponding to the biodegradable quaternary ammonium salt disinfection resin material under the above different addition conditions are shown in Figure 2. Figure 4 shown.

[0160] from Figure 4We can find that within the same reaction time, the number of pathogenic bacteria remaining in the water body decreases rapidly with the increase in the dosage of biodegradable quaternary ammonium disinfection resin material. For four different types of pathogenic bacteria, namely Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus, the removal rate of biodegradable quaternary ammonium disinfection resin material in the dosage range of 0.1 to 3 mL is between 40% and 99%. This phenomenon shows that the antibacterial behavior of biodegradable quaternary ammonium disinfection resin material is non-selective, and both Gram-negative bacteria and Gram-positive bacteria can be well removed in the contact reaction with the resin material. The positively charged quaternary ammonium group is a non-selective ligand that can attract negatively charged bacteria on the cell membrane through charge action (the isoelectric point of bacteria is generally around 1.5 to 4.5, which is lower than the isoelectric point of the environment, resulting in negative charge on the bacterial surface). On the one hand, the positively charged quaternary ammonium salt groups adsorb negatively charged bacteria through electrostatic force, hydrogen bonding force, hydrophobic binding, etc., resulting in a chamber resistance effect, which inhibits bacterial growth and causes death; on the other hand, the hydrophobic quaternary ammonium groups on the resin surface interact with the hydrophilic groups of the bacteria, changing the permeability of the membrane, and then lysing occurs, destroying the cell structure, causing cell dissolution and death, thereby removing pathogenic bacteria in the water. In addition, due to the composition of the cell membrane of pathogenic bacteria, the molecular size of the antibacterial material and the density of the quaternary ammonium salt functional group also affect the contact effect between bacteria and antibacterial materials to a certain extent.

[0161] (c) Kinetic experiment of resin sterilization behavior

[0162] Take 1mL of the prepared bacterial suspension into a 250mL sterile conical flask, dilute it to 100mL with sterile phosphate buffer solution (SPS), keep the initial bacterial solution concentration at 10CFU / mL, and add 1mL of a series of resins. Place it in a constant temperature shaking shaker for reaction, mix the resin and the water sample thoroughly, set the speed to 150r / min, and the temperature to room temperature 25°C. During the reaction, samples were taken at 10, 15, 20, 25, 30, 40, 50 and 60min respectively, and the concentration of target bacteria in the water sample was detected by the plate method to calculate the removal rate. By setting different sampling time points, the kinetic curve of the removal of pathogenic bacteria in the water body by the biodegradable quaternary ammonium disinfection resin material prepared in Example 1 was systematically studied and compared with ordinary chitosan resin and a typical commercially available contact disinfection material-silver-loaded activated carbon. The results are as follows Figure 5 shown.

[0163] from Figure 5It can be seen that common chitosan resin has almost no antibacterial activity, and its bacteria removal rate does not increase over time. Silver-loaded activated carbon and quaternary ammonium salt resin have shown obvious antibacterial activity, and the bacteria removal rate increases with the reaction time, and the cell number in the four kinds of bacterial suspensions decreases rapidly. Compared with silver-loaded activated carbon, the biodegradable quaternary ammonium salt disinfection resin material prepared in embodiment 1 shows faster sterilization kinetics to the removal process of all bacteria, particularly to Escherichia coli. In the first 10 minutes of investigating the rapid disinfection performance, about 40% of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus and more than 60% of Bacillus subtilis can be contacted and removed by biodegradable quaternary ammonium salt disinfection resin material. In contrast, common chitosan resin has only about 30% removal efficiency to Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus due to the lack of effective antibacterial groups.

[0164] (d) Experiment on the effect of water quality parameters on the sterilization behavior of resin

[0165] The experimental test of the water quality parameters involved in the present invention on the effect of the resin sterilization behavior mainly examines the effect of ionic strength, temperature and natural organic matter concentration (NOM) on the sterilization ability of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1. The influence experiments all use Staphylococcus aureus as the model bacteria, the dosage of the biodegradable quaternary ammonium salt disinfection resin material is fixed at 1 mL, and the reaction time is fixed at 1 h. Among them, the effect of ionic strength on the bactericidal ability of quaternary ammonium resin was investigated. Cl- was selected as the representative ion in the experiment. A certain amount of NaCl was added to the bacterial suspension to change the Cl- ion concentration of the water body. The dosage of NaCl was 0.5, 0.6, 0.7, 0.8, and 0.9 mg / L, respectively. After the reaction, the water samples were sampled and the number of colony counts were detected. The effect of temperature on the bactericidal ability of quaternary ammonium resin was investigated by adjusting the temperature of the constant temperature shaker in the resin adsorption test. The temperature was set to 10, 15, 20, 25, and 30°C, respectively. After the reaction, the water samples were sampled and the number of colony counts were detected. The effect of organic matter NOM concentration on the bactericidal ability of biodegradable quaternary ammonium disinfection resin materials was investigated. A certain amount of humic acid solution was added to the bacterial suspension so that the humic acid concentration of the bacterial suspension was 2, 4, 6, 8, and 10 mg / L, respectively. After the reaction, the water samples were sampled and the number of colony counts were detected. The results are as follows: Figures 6 to 8 shown.

[0166] from Figure 6It can be seen from the analysis that in the NaCl concentration range between 10~50mM, the increase of ionic strength does not affect the removal efficiency of biodegradable quaternary ammonium salt disinfection resin material to pathogenic bacteria. However, in the initial stage when the ionic strength increases, the sterilization rate of biodegradable quaternary ammonium salt disinfection resin material presents a slow downward trend, but after the ionic concentration exceeds 30mM, there is no further downward trend. In the whole ionic strength variation range, there is still more than 87% of Staphylococcus aureus to be removed. This phenomenon illustrates that, even if there is ion interference, biodegradable quaternary ammonium salt disinfection resin material of the present invention can still bring into play outstanding sterilization efficiency.

[0167] from Figure 7 The results of the study on the effect of temperature on the sterilization ability of biodegradable quaternary ammonium disinfection resin materials showed that the removal rate of Staphylococcus aureus did not change significantly within the ambient temperature range of 10 to 30°C. Although many studies have shown that as the temperature rises, the activity of bacteria increases, resulting in an increase in the contact opportunity between bacteria and antibacterial materials, thereby improving the removal rate, this phenomenon was not found in the experiments of the present invention.

[0168] from Figure 8 In the experimental results of the effect of organic matter NOM concentration on the bactericidal ability of quaternary ammonium salt resin, it can be seen that when the humic acid concentration in the solution is 2 mg / L, the antibacterial efficiency of the biodegradable quaternary ammonium salt disinfection resin material drops from 93% to 87%. However, when the concentration is further increased, the removal rate does not decrease further. Even when the humic acid concentration in the solution is 10 mg / L, more than 83% of Staphylococcus aureus are removed by the quaternary ammonium salt resin. In contrast, the disinfection effect of the typical polymer quaternary ammonium salt disinfection resin with acrylic acid as the skeleton is significantly affected by NOM. When the humic acid concentration in the solution is 2 mg / L, the antibacterial efficiency of the traditional polymer quaternary ammonium salt disinfection material has dropped to 78%. When the humic acid concentration is further increased, its removal rate drops rapidly. When the humic acid concentration is 10 mg / L, the removal rate of Staphylococcus aureus is less than 25%. In general, organic NOM is ubiquitous in water environments, rich in carboxyl and hydroxyl, and therefore can be adsorbed by positively charged quaternary ammonium salt groups, occupying adsorption sites on quaternary ammonium salt groups, while reducing the Zata potential of the material, which can weaken the electrostatic force between bacteria and the quaternary ammonium salt material, causing the decline of its antimicrobial properties. However, the biodegradable quaternary ammonium salt disinfection resin material of the present invention, through the combination of quaternary ammonium salt and chitosan, ensures the adsorption sites on the quaternary ammonium salt groups, ensures the Zata potential of the material, and then ensures that the antimicrobial properties of the biodegradable quaternary ammonium salt disinfection resin material will not decline.

[0169] 5) Resin regeneration test

[0170] After the first contact and disinfection of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 with drinking water, the water sample and the resin are separated by static sedimentation. The used biodegradable quaternary ammonium salt disinfection resin material is immersed in a 10% by mass NaCl regeneration solution and regenerated for 20 minutes. The regeneration liquid remaining inside the resin is then cleaned with ultrapure water. After cleaning, it is put into the next cycle for use. The regeneration liquid is sampled and plated to determine whether there are any residual live bacteria in the regeneration liquid. The effect of the recycled use of the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 on the removal of pathogenic bacteria in water bodies is shown in the following results. Fig. 9 shown.

[0171] Fig. 9 The results show that in 5 consecutive regeneration and reuse cycles, the antibacterial performance of the biodegradable quaternary ammonium salt disinfection resin material against pathogenic bacteria showed a slight attenuation trend after multiple regeneration cycles, and its removal efficiency decreased from 93.8% in the first use to 81.2%. This phenomenon shows that the biodegradable quaternary ammonium salt disinfection resin material has a cumulative effect during the continuous recycling process. On the one hand, the hydrophobic organic matter in the bacterial suspension blocks the resin pores. On the other hand, the microorganisms attached to the surface of the quaternary ammonium salt material are not completely desorbed during the regeneration process. There are still many microbial fragments or metabolites on the surface of the material, which reduces the recycling effect. Despite this, the quaternary ammonium salt resin used multiple times maintains a high-efficiency and stable sterilization ability. At the same time, the biosafety of the regeneration liquid was investigated. The used regeneration liquid was spread on nutrient agar plates and placed in a constant temperature incubator for overnight culture. No colonies were observed on the plates, indicating that no live bacteria remained in the resin regeneration process. Using 10% NaCl solution as the regeneration agent can not only exchange the microbial fragments adsorbed on the resin surface, but also use high osmotic pressure to lyse the residual live bacteria, thereby ensuring biosafety.

[0172] 6) Dynamic disinfection performance test

[0173] The dynamic disinfection performance test was completed by continuously flowing the raw water through the resin layer, examining the total number of bacterial colonies and the number of E. coli in the effluent water, and comparing them with the limit values ​​in the "Sanitary Standard for Drinking Water" (GB5749-2022) to evaluate the safety of the material. The biodegradable quaternary ammonium salt disinfection resin material particles prepared in Example 1 were filled in a The inner diameter of the glass tube is about 12mm, the filling volume is about 10mL, the effective height is 89mm, and the filling porosity is between 0.46 and 0.55. The schematic diagram of the dynamic disinfection performance test device and the actual photo of the filter column are shown in the figure. Fig.10As shown. Sufficient raw water samples were placed in a bucket and pumped through the resin-filled filter column using a peristaltic pump at a constant empty bed contact time (EBCT) of 5 minutes (flow rate 12 BV / h). The effluent was continuously sampled using a sterile test tube and an automatic collector, and the sampling volume was fixed at 10 mL. After sampling, each sample was diluted with a sterile phosphate buffer solution (SPS) in a gradient manner, with dilutions of 10 -1 , 10 -2 and 10 -3 . Take 100 μL of the diluted sample and drop it on the nutrient agar plate, spread it evenly, and place it in a constant temperature incubator for cultivation at 37°C for 18 hours. Select the dilution with a colony count between 15 and 150 as the counting sample of the sample and count it.

[0174] To ensure that the number of colonies is moderate, the dilution multiples used for the effluent and raw water are respectively used. The control sample is raw water that has not been treated with quaternary ammonium salt resin, and the sampling time is consistent with the effluent sample. At the same time, in order to avoid the introduction of miscellaneous bacteria to interfere with the counting results, all utensils are sterilized by high pressure before use during the experiment. Sampling, dilution and plate coating processes are all completed in a clean bench. To complete the comparative experiment and reflect the superiority of the quaternary ammonium salt resin of the present invention, this test is repeated once each under the conditions of filling the filter column with ordinary chitosan resin and commercially available silver-loaded activated carbon. The results are shown in Table 1.

[0175] Table 1 Dynamic disinfection effects of quaternary ammonium salt resin materials, ordinary chitosan resin materials, and commercially available silver-loaded activated carbon on pond water

[0176]

[0177] Among them, Table 1 shows the total colony count and coliform count of a pond water sample, as well as the biodegradable quaternary ammonium salt disinfection resin material prepared in Example 1 of the present invention, the ordinary chitosan resin material prepared in Control Example 1, and the commercially available silver-loaded activated carbon column experimental dynamic disinfection treatment of the pond water sample.

[0178] From the analysis of Table 1, it can be seen that after 60 minutes of continuous flow dynamic disinfection, the total colony count of the effluent of the quaternary ammonium salt resin layer is always below 25CFU / mL, and coliform bacteria are not detected, which meets the limit requirements of the "Sanitary Standard for Drinking Water" (GB5749-2022), and compared with the commercially available silver-loaded activated carbon contact disinfection filter material, the sterilization rate of the quaternary ammonium salt resin is significantly better, which reflects that the biodegradable quaternary ammonium salt disinfection resin material particles of the present invention have a stronger antibacterial effect, thereby proving that it is suitable for disinfection of actual drinking water bodies.

[0179] 7) Resin degradation test

[0180] The evaluation of the resin degradation performance is carried out by a simple natural soil landfill weighing method. Take 5 grams of the biodegradable quaternary ammonium salt disinfection resin prepared in Example 1, the ordinary chitosan resin prepared in Control Example 1, and the high molecular weight quaternary ammonium salt disinfection material prepared in Control Example 2, and respectively fill them into 1 kg of farmland soil obtained from the same location. The landfilled soil is placed in a plastic flower pot and placed in a 35°C environmental test box. The landfilled soil is weighed every week and the reduction in resin mass is recorded. The results are shown in FIG. Fig.11 shown.

[0181] Fig.11 In the embodiment, chitosan corresponds to the common chitosan resin prepared in control example 1, acrylic acid corresponds to the high molecular weight quaternary ammonium salt disinfection material prepared in control example 2, and degradable corresponds to the biodegradable quaternary ammonium salt disinfection resin prepared in embodiment 1.

[0182] from Fig.11 It can be seen that the biodegradable quaternary ammonium salt disinfection resin prepared by the present invention has good biodegradation properties like ordinary chitosan cross-linked polymers. After 8 weeks of landfill, the mass of the resin itself is reduced by more than 50% by soil microorganisms, and has the potential for natural landfill degradation and low secondary pollution risk. In contrast, the typical acrylic acid skeleton is not easy to biodegrade, and the polymer quaternary ammonium salt disinfection material itself is too stable, and the mass reduction after 8 weeks of landfill is less than 2%.

[0183] In summary, the biodegradable quaternary ammonium disinfection resin material of the present invention is prepared by pre-quaternization reaction before reverse cross-linking polymerization, using quaternized chitosan slurry as a continuous phase to produce a quaternized chitosan cross-linked resin with antibacterial and disinfection functions. The positively charged quaternary ammonium salt group on the resin surface can adsorb negatively charged bacteria through electrostatic force, hydrogen bond force, hydrophobic binding and other effects, produce a chamber resistance effect, and cause bacterial growth to be inhibited and die; at the same time, the quaternary ammonium group acts on the hydrophilic group of the bacteria, changes the permeability of its cell membrane, and then lyses, destroys the cell structure, causes the dissolution and death of the bacteria, and thus removes the pathogenic bacteria in the water body. The introduction of quaternary ammonium salt groups improves the pore structure of the polymer and strengthens the polymer's capture of pathogenic bacteria in water. Experiments have shown that quaternary ammonium salt drinking water disinfection resin materials have good adsorption properties in the pH range of 4 to 10, and the disinfection performance is less affected by ionic strength, temperature and natural organic matter in water within the common water quality range, and has good adaptability to water environment. At the same time, the sterilization rate after 5 cycles of disinfection and regeneration is still higher than 85%, showing good cyclic regeneration performance. Therefore, using quaternary ammonium salt chitosan polymer resin particles as contact disinfection filter materials for emergency water purification devices can effectively serve as a biological safety barrier.

[0184] The preparation method of the biodegradable quaternary ammonium salt disinfection resin material of the present invention adopts the biomass material chitosan as the matrix, so that the resin has good biocompatibility, is easy to directly dispose of the waste resin in the environment, avoids secondary pollution, and the preparation method has the advantages of simple operation, mild conditions and low cost, and has potential application value in the field of drinking water treatment technology.

[0185] The above embodiments are only preferred implementations of the present invention, and the protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention.

Claims

1. A biodegradable quaternary ammonium salt disinfection resin material, characterized in that: It includes a resin skeleton and a quaternary ammonium salt group doped in the resin skeleton; The raw material of the resin skeleton is selected from adhesive materials; The adhesive material is selected from at least one of chitosan, carrageenan and sodium alginate.

2. The biodegradable quaternary ammonium salt disinfection resin material according to claim 1, characterized in that: The quaternary ammonium salt disinfection resin material is obtained by inverse emulsion polymerization of the adhesive material and the quaternary ammonium salt.

3. The biodegradable quaternary ammonium salt disinfection resin material according to claim 2, characterized in that: The quaternary ammonium salt is selected from at least one of 2,3-epoxypropyltrimethylammonium chloride, didodecyldimethylammonium chloride and benzyltrimethylammonium chloride.

4. The biodegradable quaternary ammonium salt disinfection resin material according to claim 2, characterized in that: The mass ratio of the adhesive material to the quaternary ammonium salt is 100:2-10.

5. A method for preparing a biodegradable quaternary ammonium salt disinfection resin material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1, dissolving the adhesive material in an organic acid solution to obtain an adhesive aqueous solution; S2, adding a quaternary ammonium salt to the adhesive aqueous solution to obtain a quaternary ammonium salt adhesive slurry; S3, adding a continuous phase solvent, a pore-forming agent, an emulsifier and an initiator to the quaternized adhesive slurry to obtain a mixed slurry, and continuously heating the mixed slurry during the process of adding the continuous phase solvent, the pore-forming agent, the emulsifier and the initiator, stirring the reaction once, and promoting the reverse emulsion polymerization of the mixed slurry into a droplet system; S4, adding an alkaline solution to the droplet system and continuing to raise the temperature to a second temperature, stirring a second time to carry out a cross-linking reaction, so as to cause the droplets to solidify into particles, and obtain a quaternary ammonium salt disinfection resin material.

6. The preparation method according to claim 5, characterized in that: The solid-liquid ratio of the adhesive material to the organic acid is 1 g to 10 g: 100 mL; And / or, the organic acid solution is selected from at least one of a formic acid solution, an acetic acid solution and a propionic acid solution; And / or, the volume concentration of the organic acid in the organic acid solution is 1-3%; And / or, S2 includes: adding a quaternary ammonium salt to the adhesive aqueous solution, reacting at room temperature for 0.5 to 4 hours, and obtaining a quaternary ammonium salt adhesive slurry.

7. The preparation method according to claim 5, characterized in that: The continuous phase solvent is selected from an organic solvent that is less dense than water and immiscible with water; and / or, the continuous phase solvent is selected from at least one of liquid paraffin, mineral oil, silicone oil and synthetic hydrocarbons; And / or, the volume ratio of the continuous phase solvent to the quaternized adhesive slurry is 1:3 to 2:1; and / or, the pore-forming agent is selected from liquid organic matter that is volatile and insoluble in water; And / or, the pore-forming agent is selected from at least one of ethyl acetate, chloroform and styrene; and / or, the volume ratio of the pore-forming agent to the mixed slurry is 2-10:100; and / or, the emulsifier is selected from ester nonionic surfactants; and / or, the emulsifier is selected from at least one of Tween 20, Tween 40, Tween 60, Tween 80, Span 20, Span 40, Span 60, Span 80, sucrose fatty acid esters, propylene glycol fatty acid esters and mono- and di-stearoyl glycerides; and / or, the volume ratio of the emulsifier to the mixed slurry is 1 to 6:100; And / or, the initiator is selected from agents that can react with amino groups on the adhesive material to form a Schiff base reaction; and / or, the initiator is selected from at least one of formaldehyde, acetaldehyde, malondialdehyde, glutaraldehyde, propylene oxide, epichlorohydrin and epoxy alcohol; And / or, the volume ratio of the initiator to the mixed slurry is 3-15:

100.

8. The preparation method according to claim 5, characterized in that: The temperature is continuously raised between 40 and 60° C. during the process of adding the continuous phase solvent, pore former, emulsifier and initiator; And / or, the second temperature is 70°C to 85°C; And / or, the rotation speed of the primary stirring reaction is 400-900 rpm; And / or, the time of the stirring reaction is 30 to 220 minutes; And / or, the rotation speed of the secondary stirring reaction is 200-400 rpm; And / or, the secondary stirring reaction time is 2 to 6 hours; And / or, in S4, the alkaline solution is added dropwise; And / or, the alkaline solution is selected from at least one of a potassium hydroxide solution, a sodium hydroxide solution and an ammonia solution; and / or, the concentration of the alkali in the alkaline solution is above 1 mol / L; And / or, the pH value of the alkaline solution is greater than 12.

5.

9. An application of a biodegradable quaternary ammonium salt disinfection resin material obtained by the preparation method according to any one of claims 5 to 8, characterized in that: The biodegradable quaternary ammonium salt disinfection resin material is used as a contact disinfection material in drinking water.

10. The use according to claim 9, characterized in that: The biodegradable quaternary ammonium salt disinfection resin material is directly landfilled and biodegrades by itself after it becomes ineffective, so as to achieve harmlessness throughout the entire life cycle of the material.